Crescimento e produção de clones de Eucalyptus saligna Smith sob diferentes condições ambientais - Pissinin, Lucas Zancan (2013)
This study had as objective to analyze the differences in the dominant hight (h100) growth trends of two Eucalyptus saligna Smith clones, implanted on different conditions of soil and relief. The differences due this variable growth were used to separate both clones in distinct growth groups, and this way to classify the sites to each group, to adjust, validate and organize a set of functions such as number of trees per hectare (N), average quadratic diameter (dg), basal area and commercial volumes with and without bark, building this way a whole stand prognosis system to the evaluated clones. The analysis of growth trends defined tree different groups: The first one encompassing the clone 2864 implanted on hight quality soils (Group I), the second one the same clone 2864 but implanted on medium and low quality soils (Group II), and the third one that consisted in the clone 4039 on all soil classes (Group III), which did not show the same growth difference among the soil classes as the clone 2864 did. The variables altitude and slope, even showing some significant differences in the analysis, did not justify the separation in distinct groups. The analysis of number of trees per hectare showed different pattern between both clones, but did not between both groups based on 2864 clone, sharply indicating that this pattern is due the genetic characteristics of each clone. Among the stand density interval analyzed (700 to 1500 trees per hectare) the fitted equation estimated adequately, did not showing different mortality trends as the stand density changed. The average quadratic diameter was modeled by the variables dominant hight (h100), N and age for all groups in conjunction, did not requiring an specific function to each growth group to estimate accurately the average diameters. Basal area and volumes with and without bark were modeled by the previous variables (h100, N and dg) and showed different trends among the three groups. The final yield was highly superior in the group I, followed by the group II and after by the group III. The age of maximizing production (AMP) was distinct among each group and, the smaller AMP were found in the best sites to all groups. AMP values, from the best to the worst site, fluctuated from 9,5 to 12 years, from 8,5 to 10,5 years and from 7 to 8,4 years for the groups I, II and III, respectively. This study allowed concluding that there are differences in the growth and yield, not only between the two evaluated clones, but also between the different soils classes.